2003
DOI: 10.1016/s0735-1097(02)02860-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac fibrosis occurs early and involves endothelin and AT-1 receptors in hypertension due to endogenous angiotensin II

Abstract: In Ang II-dependent hypertension, cardiac fibrosis was associated with LV hypertrophy and was hindered by both mixed ET(A)/ET(B) blockade and AT-1 blockade. Only the latter treatment prevented both hypertension and LV hypertrophy. Thus, there is a dissociation between the mechanisms of cardiac fibrosis and hypertension, which do and do not entail ET-1, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 37 publications
6
65
0
1
Order By: Relevance
“…8 Also, this dose resembles that used by other authors. 26,11,27 Our present results are in agreement with our previous findings that nonselective ET receptor blockade with bosentan improved survival rate but had no effect on the course of hypertension in homozygous 8 or heterozygous TGR. 11,10 Similarly, Karam et al 28 also found that the renoprotective actions of bosentan were independent of any BP-lowering effect.…”
Section: Discussionsupporting
confidence: 93%
“…8 Also, this dose resembles that used by other authors. 26,11,27 Our present results are in agreement with our previous findings that nonselective ET receptor blockade with bosentan improved survival rate but had no effect on the course of hypertension in homozygous 8 or heterozygous TGR. 11,10 Similarly, Karam et al 28 also found that the renoprotective actions of bosentan were independent of any BP-lowering effect.…”
Section: Discussionsupporting
confidence: 93%
“…Whether RVH that occurs during chronic hypoxia results from ET-1 synthesis in RV cardiomyocytes has yet to be determined. Interestingly, LVH in heterozygous male Ren2 rats is ET-1 dependent in older (12-to 16-wk-old) rats and younger rats on a high-salt diet, but not in younger (6-to 9-wk-old) rats on a normal-salt diet (50,56,61), similar to those used in the present study. We speculate that RVH in heterozygous male Ren2 rats is more dependent on the endothelin system than LVH and that the endothelin system in the RV is not fully activated in younger rats.…”
Section: Methodological Considerationssupporting
confidence: 62%
“…7). Periarterial fibrosis has been reported in these transgenic rats as young as 8 -9 wk of age (28,31), and extensive interstitial fibrosis and scarring have been reported in 13-to 14-wk-old Ren2 rats (23). The myocardium of 10-to 11-wk-old Ren2 male rats studied here exhibited modest interstitial fibrosis.…”
Section: Discussionsupporting
confidence: 46%